2020
DOI: 10.1002/med.21771
|View full text |Cite
|
Sign up to set email alerts
|

The role of hypoxia‐inducible factor 1 in tumor immune evasion

Abstract: Hypoxia‐inducible factor 1 (HIF‐1) plays an indispensable role in the hypoxic tumor microenvironment. Hypoxia and HIF‐1 are involved in multiple aspects of tumor progression, such as metastasis, angiogenesis, and immune evasion. In innate and adaptive immune systems, malignant tumor cells avoid their recognition and destruction by HIF‐1. Tumor immune evasion allows cancer cells to proliferate and metastasize and is associated with immunotherapy failure and chemoresistance. In the hypoxic tumor microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 129 publications
(238 reference statements)
1
146
0
Order By: Relevance
“…Multiple oncogenic pathways that were strongly associated with tumor progression, chemotherapeutic resistance, and immune cell infiltration were enriched. Biological processes and pathways, including but not limited to the PI3K-AKT signaling pathway, HIF-1 signaling pathway, and glycolysis, were all implicated in the regulation of malignant behavior and anticancer immunity (Xu et al, 2021b;Kobayashi et al, 2020;Sun and Meng, 2020;You et al, 2020). These findings could partly explain how the risk score affected patient survival and immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple oncogenic pathways that were strongly associated with tumor progression, chemotherapeutic resistance, and immune cell infiltration were enriched. Biological processes and pathways, including but not limited to the PI3K-AKT signaling pathway, HIF-1 signaling pathway, and glycolysis, were all implicated in the regulation of malignant behavior and anticancer immunity (Xu et al, 2021b;Kobayashi et al, 2020;Sun and Meng, 2020;You et al, 2020). These findings could partly explain how the risk score affected patient survival and immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it has been reviewed that hypoxia induces immunosuppressive process by affecting immune cell transport and angiogenesis in the tumor microenvironment, and provides a basis for clinical monitoring (Augustin et al, 2020;Pietrobon and Marincola, 2021). More specifically, potential mechanisms by which HIF-1 signaling in the tumor microenvironment promotes immune escape and leads to poor prognosis include: induction of immunosuppressor and immune checkpoint molecule expression, autophagy, exosome release, and novel immunogenic cell death (Vito et al, 2020;You et al, 2020). Studies on COAD have shown that hypoxia promotes immunosuppression by inhibiting the differentiation of CD4 + effector T cells and enhancing the activity of regulatory T cells (Westendorf et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional and growth factors are also implemented during oncogenesis via a modification of the immune response. Hypoxia-inducible factor 1 (HIF-1) plays an indispensable role in the hypoxic tumor microenvironment [9].…”
Section: Of 10mentioning
confidence: 99%